2016
DOI: 10.1039/c6ee00456c
|View full text |Cite
|
Sign up to set email alerts
|

Designing thermoelectric generators for self-powered wearable electronics

Abstract: Computational efficient, quasi-3D model for designing body wearable thermoelectric generators and experimental verification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
303
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 348 publications
(311 citation statements)
references
References 24 publications
6
303
0
2
Order By: Relevance
“…Suarez et al showed that when the material ZT is fixed, as the thermal conductivity of the material decreases, power density generated from body heat increases [20]. However, while this result emphasizes the importance of material thermal conductivity in device simulations, it does not suggest how this affects the engineering of the materials.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…Suarez et al showed that when the material ZT is fixed, as the thermal conductivity of the material decreases, power density generated from body heat increases [20]. However, while this result emphasizes the importance of material thermal conductivity in device simulations, it does not suggest how this affects the engineering of the materials.…”
Section: Introductionmentioning
confidence: 64%
“…In previous research, it was shown that low thermal conductivity is advantageous for energy harvesting on the human body while the ZT remains at the same value [20]. However, in the practical engineering of a material, such as doping level control, ZT also changes while the thermal conductivity is adjusted [39].…”
Section: Carrier Concentration Difference Between Maximum Zt and Maximentioning
confidence: 99%
See 3 more Smart Citations